Role of Socio-Technical Assistance (STA) in Private Housing Reconstruction for Vulnerable Community (A case study of Okhaldhunga District, Nepal) - Karki, Tej Bahadur; Lamsal, Rita; Poudel, Namita (Nepal Journal of Multidisciplinary Research, 2020)
Vulnerability is such stage when such people and group can be easily harmed physically or emotionally. They are always in risk in natural or man-made disaster so such people and groups should be cared and supported by all concerns. Great earthquake of August 2015, many old age people, poor, single women, child-headed family and disable family become vulnerable in earthquake affected districts of Nepal. So, Nepal Government had deployed the Socio-Technical Assistance (STA) team to support the vulnerable households. The main objective of this study was to identify the role of STA in private housing reconstruction of vulnerable household. The study was conducted in Okhaldhunga district among the 35 vulnerable households. The study was based on the mixed method so both quantitative and qualitative method was used to collect the data. The findings show that majority of ethnic group who were more than 70 years old were in urgent need of support who were fully supported by STA. almost all beneficiaries were happy with the support and behaviour of STA. economically, 44.1% household had spent more than 3 Lakh to build the house so they had to manage the additional amount. They had taken loan from relative and neighbor so Nepal Government should provide livelihood support to such household to improve their socio-economic status.